Pago, dunque sono (cittadino europeo) Il futuro dell'UE tra responsabilità fiscale, solidarietà e nuova cittadinanza europea - Campus, Mauro; Dorigo, Stefano; Federico, Veronica; Lazzerini, Nicole (Studi e saggi, 2022)
The book collects the contributions of a group of scholars, with different scientific backgrounds, on the issue of the relationship between taxation, solidarity and citizenship within the EU. The common thread linking them is the inescapability of the tax duty in a community of rights and the incompleteness of the European system, which performs important functions of collective interest without claiming any cost for those who use it. What emerges is the need for a genuine EU own tax, which, without the intermediary of the Member States, would burden the users of European public goods, increasing awareness of the social value of the EU, amplifying its solidarity dimension, and outlining a new concept of citizenship. In short, I pay, therefore I am (European citizen).